KAJIAN KARYA SENI KUDA UGO UNTORO - Rumekso, Kunto Adi (Jurnal Industri Kreatif dan Inovatif, 2024)
The research describes the equine artworks of Ugo Untoro, an artist from Yogyakarta who is famous for his horse-themed paintings and installations due to his love and respect for horses. The freedom, in this case an anti-style of thought in art seems to be a distinctive distinction Ugo has compared to other artists, as well as his pure and fiery emotions that enliven each of his works. The ability to capture the essence of life, experience is also the main ingredient in formulating a work of art, as well as in processing it to create a creativity, in this case in creating art. The understanding of painting techniques combined with the background story and experiences that inspire him make Ugo Untoro's works increasingly known by many people, both at home and abroad. Horses are seen by the public only as animals that help humans to alleviate certain human jobs and are considered only as animals that live according to their nature instinct until they die, but for Ugo Untoro they have their own value and are like humans or even heroes who sacrifice their energy to die as forgotten heroes. This research explains that how horses inspire Ugo Untoro in his work and how art can be a medium for him to tell people about his aspirations and thoughts.